Resident Immune Cells of the Liver in the Tumor Microenvironment - Lu, Yunjie; Ma, Shiying; Ding, Wei; Sun, Pengcheng; Zhou, Qi; Duan, Yunfei; Sartorius, Kurt (Frontiers in Oncology, 2022)
The liver is a central immunomodulator that ensures a homeostatic balance between protection and immunotolerance. A hallmark of hepatocellular carcinoma (HCC) is the deregulation of this tightly controlled immunological network. Immune response in the liver involves a complex interplay between resident innate, innate- like and adaptive immune cells. Immune response in the liver is modulated by its continuous exposure to toxic molecules and microorganisms that requires a degree of immune tolerance to protect normal tissue from damage. In HCC pathogenesis, immune cells must balance a dual role that includes the elimination of malignant cells, as well as the repair of damaged liver tissue to maintain homeostasis. Immune response in the innate and adaptive immune systems extends to the crosstalk and interaction involving immune-regulating non-hematopoietic cells, myeloid immune cells and lymphoid immune cells. In this review we discuss the different immune responses of resident immune cells in the tumor microenvironment. Immune cell pathways need to be better understood although immunotherapy innovations have provided some exciting innovations, however, current FDA-approved targeted therapies have produced modest results to date for the treatment of advanced HCC. In this review article we summarize the roles of specific resident immune cell subsets and their crosstalk subversion in HCC pathogenesis, with a view of identifying potential new biomarkers and therapy options.